Local ecological knowledge and fisheries management: a study among riverine fishing communities in Kerala, India - Sunil D. Santha (Local Environment Vol. 13, No. 5, 423-435, July 2008, 2008)
This paper explores and analyses how local ecological knowledge as a component of culture facilitates sustainable resource management practices among riverine fishing communities in Kerala, India. The paper is based on a comparative ethnographic analysis between a heterogeneous fishing village and a homogeneous fishing village within the Pamba-Achankovil River Basin. Key observations from analysis show that various groups of fishermen give emphasis to different knowledge spheres based on the nature of the resources and the type of fishing gear they are familiar with. Local knowledge among the fishing communities plays a crucial role in the sustainable management of fishery resources. However, this local knowledge serves the purpose of sustainable resource management only when it is supplemented by the other components of culture.